Aortic carboxypeptidase-like protein regulates vascular adventitial progenitor and fibroblast differentiation through myocardin related transcription factor A - Wang, Dahai (Sci Rep, 2021)
The vascular adventitia contains numerous cell types including fibroblasts, adipocytes, inflammatory cells, and progenitors embedded within a complex extracellular matrix (ECM) network. In response to vascular injury, adventitial progenitors and fibroblasts become activated and exhibit increased proliferative capacity and differentiate into contractile cells that remodel the ECM. These processes can lead to vascular fibrosis and disease progression. Our previous work established that the ECM protein aortic carboxypeptidase-like protein (ACLP) promotes fibrotic remodeling in the lung and is activated by vascular injury. It is currently unknown what controls vascular adventitial cell differentiation and if ACLP has a role in this process. Using purified mouse aortic adventitia Sca1+ progenitors, ACLP repressed stem cell markers (CD34, KLF4) and upregulated smooth muscle actin (SMA) and collagen I expression. ACLP enhanced myocardin-related transcription factor A (MRTFA) activity in adventitial cells by promoting MRTFA nuclear translocation. Sca1 cells from MRTFA-null mice exhibited reduced SMA and collagen expression induced by ACLP, indicating Sca1 cell differentiation is regulated in part by the ACLP-MRTFA axis. We determined that ACLP induced vessel contraction and increased adventitial collagen in an explant model. Collectively these studies identified ACLP as a mediator of adventitial cellular differentiation, which may result in pathological vessel remodeling.